Struktura zużycia czasu w gospodarstwach chłopskich - Borowski, Stanisław (Wydział Prawa i Administracji UAM, 1966)
The time budget structure on peasant farms has been divided in five groups, i.e. working hours devoted to: agricultural production, household activities, non- -agricultural occupation, personal-leisure time and finally nightly sleep. This time spending has been combined with the characteristic features of the examined farms and with the persons actively engaged on them. The farms have been divided into two groups — the first one comprising farms which constitute the main source of income and the second one comprising farms which constitute an additional source of income. Each of these two groups has been further divided into area groups. The farm population has been classified according to sex, vocationally active and passive persons and according to performed functions in the farms. The seasonal changeability of time structure is illustrated by samples taken in February, May, August, October and December. The regional differentiation is being characterized by two specific regions: mid-western and mid-eastern. Excluding the group of farms of an area of 0,5—2 hectars in the category of farms which constitute the main source of income, the time devoted by farming and vocationally active menfolk to agricultural production — exceeds 7 hours daily. In the periods of summer and autumn culminations — the working hours fluctuate around 12 hours. The working time of the landladies, permanently helping family members and vocationally active womenfolk in the months of May, August and October fluctuates around 7 hours and in February and December around 3 hours. According to observations undertaken in May, August and October, the time spent in household activities by landladies, permanently helping family members and vocationally active women is generally shorter than the time devoted to agricultural production. In February and December this relation is usually reversed. The time spent in household activities undergoes also some seasonal changes. The time devoted to non-agricultural earning activities decreases with the increase in the farms areas. All the groups of the peasant population take part in these activities. The farmers devote as a rule more time for personal leisure than the landladies, the family members who help sporadically more than those who help permanently. Also the hours of the nightly sleep varies according to the category of persons. In the farms which constitute the main source in income — the nightly sleep amounts to 7 hours and more, whereas in the farms which constitute an additional source of income — to 6 hours and sometimes even less. The research in the field of the time-spending structure in the peasant farms may be useful in the assessment of labour force reserves in said farms, in working out the labour force balance and in ascertaining the real working burden of the various category of persons in the different groups of farm areas. It may also be useful for the rural social and cultural policies and for specific scientific purposes e. g. the statistical classification of peasant population.